2005
DOI: 10.3748/wjg.v11.i39.6125
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of counterattack of colorectal cancer cell by Fas/Fas ligand system

Abstract: Colon cancer cells can escape the immune surveillance and killing via decreasing Fas expression, and can counterattack the immune system via increasing FasL expression. Fas/FasL can serve as potential targets for effective antitumor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…We used fluorescence microscopy to observe the shape of apoptosis in Jurkat cells induced by SW480 cells. Condensation 6.48 ± 0.31* 10 - 6 8.76 ± 0.27* 10 - 5 11.12 ± 0.35** 10 - 4 14.28 ± 0.41** ATRA, all-trans retinoic acid. Here, the relative activity of alkaline phosphatase was considered as the differentiation indicator, excluding the influence of cell numbers.…”
Section: Colon Cancer Cell-mediated Killing Of Jurkat Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used fluorescence microscopy to observe the shape of apoptosis in Jurkat cells induced by SW480 cells. Condensation 6.48 ± 0.31* 10 - 6 8.76 ± 0.27* 10 - 5 11.12 ± 0.35** 10 - 4 14.28 ± 0.41** ATRA, all-trans retinoic acid. Here, the relative activity of alkaline phosphatase was considered as the differentiation indicator, excluding the influence of cell numbers.…”
Section: Colon Cancer Cell-mediated Killing Of Jurkat Cellsmentioning
confidence: 99%
“…It has been noted that certain chemotherapeutic drugs could affect the expression of Fas and FasL in cancer cells. The up-regulation of FasL by some chemotherapeutic drugs may limit their efficacy by inducing 'immune counterattack' of cancer cells for TILs [5]. The aims of this study were to observe the influence of popularly used antitumor drugs , mitomycin (MMC), cisplatin (CP) and all-trans retinoic acid (ATRA)] on the expression of the Fas system (especially FasL) in SW480 colon cancer cells and study its probable mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Belluco et al [12] presented the results in which FasL expression showed a linear correlation with cancer progression from hyperplastic polyps to advanced colorectal carcinoma (pT4). Zhu et al [13] also observed high FasL expression in 84.9% of colorectal cancers as compared to normal glandular epithelium (3.75%), and lower Fas receptor expression in 43.4% of colorectal cancer cases than in normal epithelium (73.3%). Thus, low expression of Fas receptor in cancer cells may suggest that the Fas/FasL pathway inducing apoptosis in these cells was reduced or eliminated.…”
Section: Discussionmentioning
confidence: 97%
“…Their presence in the vicinity of neoplastic infiltration and the presence of high FasL expression in cancer cells seem to reflect the defense mechanism of cancer cells against anticancer immune cells. This was suggested by Okada [14] and Zhu [13], who investigated apoptosis in tumor-infiltrating lymphocytes (TILs). They demonstrated that apoptosis in TILs increased with higher expression of FasL protein in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called "Fas counterattack model", has been proposed to explain tumor cell immune escape [7]. Evidence for this hypothesis has been reported in renal, gastric and colon cancer [8]. However, some tumor cells, including pancreatic cancer cells and melanoma cells, do not express FasL [9,10].…”
Section: Introductionmentioning
confidence: 98%